Self‐reported dual sensory impairment, dementia, and functional limitations in Medicare beneficiaries. Issue 12 (3rd September 2021) - Assi, Lama; Ehrlich, Joshua R.; Zhou, Yunshu; Huang, Alison; Kasper, Judith; Lin, Frank R.; McKee, Michael M.; Reed, Nicholas S.; Swenor, Bonnielin K.; Deal, Jennifer A.
Abstract: Background: Vision and hearing impairments often co‐exist with dementia, and all are independently associated with limitations in daily activities. Our aim was to examine the association of dual sensory impairment with functional limitations, and further examine the combined estimated association of sensory impairment and dementia with these functional limitations. Methods: Cross‐sectional analysis of the National Health and Aging Trends Study (NHATS), a population‐based cohort of Medicare beneficiaries, was performed. Participants were selected from the 2015 round. Survey weighted Poisson regression models adjusted for dementia, demographics, and health status variables examined the association of self‐reported dual sensory impairment (no sensory impairment, single sensory impairment, dual sensory impairment) with scores of limitations in mobility, self‐care, and household activities. Models were repeated to take into account the combined effects of dual sensory impairment and dementia. Results: Overall, 7124 participants representative of Medicare beneficiaries 65 years or older were included. Of them, 43.9% were 75 years or older and 55.3% were female. Older adults with dual sensory impairment had greater limitations with mobility (prevalence rate ratio [PRR] = 1.45, 95% CI = 1.28–1.63), self‐care (PRR = 1.41, 95% CI = 1.25–1.59), and household activities (PRR = 1.54, 95% CI = 1.37–1.72) compared with those without sensory impairment. They also had greater limitations than those with a single sensory impairment across the different activity categories. In models taking into account the combined estimated effect of both sensory impairment and dementia, those with dual sensory impairment and dementia had greater limitations than those without sensory impairment or dementia in each category (mobility: PRR = 1.85, 95% CI = 1.59–2.14, self‐care: PRR = 1.86, 95% CI = 1.59–2.18, household: PRR = 2.41, 95% CI = 2.09–2.77). Conclusions: Older adults with dual sensory impairment had greater functional limitations compared with those without sensory impairment and those with a single sensory impairment. Strategies to improve visual and/or hearing function (e.g., sensory aids, rehabilitation) could potentially help prevent or minimize disability, even among those with dementia.